Template-directed synthesis of sulphur doped NiCoFe layered double hydroxide porous nanosheets with enhanced electrocatalytic activity for the oxygen evolution reaction. Issue 7 (31st January 2018) - Cao, Li-Ming; Wang, Jia-Wei; Zhong, Di-Chang; Lu, Tong-Bu
Abstract : The development of readily available, highly efficient and stable electrocatalysts for the oxygen evolution reaction (OER) is extremely significant to facilitate water splitting for the generation of clean hydrogen energy. Abstract : The development of readily available, highly efficient and stable electrocatalysts for the oxygen evolution reaction (OER) is extremely significant to facilitate water splitting for the generation of clean hydrogen energy. Layered double hydroxides (LDHs) exhibit promising electrocatalytic performance for the OER. However, their electrical conductivity and active sites should be increased for the preparation of more effective OER electrocatalysts based on LDHs for large-scale applications. Herein, we demonstrate a facile and practical pathway for the hierarchical fabrication of three-dimensional (3D) porous sulphur incorporated NiCoFe LDH nanosheets (S-NiCoFe LDH) on carbon cloth (CC). The as-obtained hierarchically structured S-NiCoFe LDH electrode shows superb electrocatalytic activity and stability for the OER, requiring overpotentials as low as 206 mV and 258 mV to achieve current densities of 10 mA cm −2 and 100 mA cm −2 in 1.0 M KOH solution, respectively, making S-NiCoFe LDH one of the most efficient low-cost electrocatalysts for the OER. The enhanced electrocatalytic performance is attributed to the unique 3D hierarchical nanostructure and sulphur doping, which endow the self-supported S-NiCoFe LDH electrode with abundant active sites and superb electrical conductivity. The strategy expands the possibilities for boosting the catalytic activity of LDH-based OER electrocatalysts.